Effect of anthrapometric factors on semen quality: a prospective cohort study - Jayakumar, Nandhini; Shankar, Kundavi; Asokan, Yamini; V., Geetha; G. V., Rashmi; Naaram, Nithya M.; K. R., Hema Niveda; Devarajan, Sandhya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Aim was to evaluate the association between anthropometric factors and semen parameters. Prospective analysis of relation between the anthrapometric factors and semen parameters of male patients attending the OPD for infertility evaluation in institute of reproductive medicine, Madras medical mission hospital, Chennai Methods: Male patients attending the OPD from December 2023 to May 2024. The study included 105 patients according to inclusion criteria whose age, height (cm), weight (kg), body mass index (BMI) (kg/m2), waist circumference (WC) (cm), hip circumference (cm) and waist hip ratio (WHR) were measured in their first visit and compared with seminal volume, concentration, count, total motility and morphology. Results: In this study as the age increases, the sperm concentration, count and total motility is found to be deteriorating. However, the volume and morphology does not have any association. BMI was found to have inverse relation with the seminal parameters and statistical association with the sperm concentration, count, total motility and morphology. The sperm concentration, count and morphology were found to be reducing with increased WC. WHR affects the concentration, motility and morphology negatively. Conclusions: This study concluded that age and BMI statistically has negative correlation on semen parameters, however measures of central obesity like WC and WHR does not have any statistical correlation with the semen parameters.